Metabolomic Analysis of Blood and Urine to identify Alcohol-Dependence Biomarkers - Mostafa, Hamza Mohamed Amin; Mostafa, Arwa Mohamed Amin; Arif, Nor Hayati; Chin, Hoe Teh; Murugaiyah, Vikneswaran a/l; Ibrahim, Baharudin (2014)
The clinical diagnosis of alcohol-dependence (AD) currently relies on AD assessment questionnairesand biomarkers such as Carbohydrate-DeficientTransferrin (CDT), Gamma Glutamyl Transferase (GGT) and Phosphatidylethanol (PEth). However, both methods of diagnosis lackspecificity and sensitivity. Metabolic fingerprinting using nuclear magnetic resonance spectroscopy (NMR)of plasma may give us a novel andaccurate method for the diagnosis of the disease. Our primary objective was to identify the metabolites/biomarkers that could discriminate between subjects diagnosed asAD, social drinkersnon-dependent and healthy control.